(3bhGYO ePgH GdEeGe eGdcs - (3eMeO Hf YHO GdQMef Hf jhSa GdecfGSjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUdi Gddg Ydi SjOfG hehdGfG eMeO hBdg hUMHg hSde gPg bhGYO GdEeGe eGdc QMeg Gddg JYGdi fXegG eMeO Hf YHO GdQMef Hf jhSa Cbhd HYO MeO Gddg ChdkG Ydi fYe CSOi EdjfG s
(3BNQgG (B:s
(3GdMeO Gddg hMOg gPg GdWQI GdJi WQQJ efgG gPg GdGejI ef TGQY SjO CMeO Hf jMji GdhfTQji Ydi bhGYO GdEeGe eGdc QMeg Gddg s
(3GdeNWhW eaccs
(3hcJHJ YfGhjjf GdaUhd HGdMHQ GdCMeQs
(3HChQGbg KbhH CVGYJ HYV GdcdeGJs
(3hYdjgG JUhjHGJ bdjdI s
(3HgG fXGe GdJYbjHI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs